New technologies and the education of information professionals - Catherine HARE (Ediciones Universidad de Salamanca, 2016)
Using the example of the Masters in Records Management by Distance Learning at the University of Nortumbria at Newcastle in the United Kingdom, the article will explore the potentials of the new information and communication technologies and the implications for using them as a means of delivery for education for information professionals. The key challenge is to ensure that the education instils not only an awareness of the technologies and skills in their use but also the capacity to understand and evaluate their potential since they are the prime tools of trade for information professionals today. An effective approach is to study the technologies through using the technologies but success can only be achieved if the wider systems of processes and approaches, based on teamwork, are developed to recognise specialisms and divisions of labour.